ISTILAH-ISTILAH MAKANAN DALAM BAHASA INGGRIS DAN BAHASA MANGE (SUATU ANALISIS KONTRASTIF) - DORSAYA, MELKI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This study is written as an attempt to describe, analyze and contrast the terms of food in English and Mange language. The English data are collected from several English books and internet whereas the Mange Language data are collected from informants The descriptive method is used to describe and analyze the kinds of food by using Frisch in Hickerson’s theory. After describing the kind of food in English and Mange language, the writer makes a contrastive analysis by using Robert Lado’s theory in finding out the similarities and differences of both languages. The result shows that the kind of  terms of food in English and Mange language consist of two groups, they are solid food and beverages/drinks. Solid food consist of fruits, vegetable, bread, meat, fish and sea food, and cooked food. Beverages/drinks consist of alcoholic and non-alcoholic drink.   Keywords: The terms of food in English, Mange Language, A Contrastive Asnalysis